Percepção dos residentes de educação física sobre o envolvimento dos alunos imigrantes nas aulas de Educação Física Escolar - Vieira, Eduardo da Silva (Brasil, 2025)
The Pedagogical Residency Program (PRP) is seen as a foundation for building future teachers, it encourages the articulation between theory and practice, in the training of teachers for basic education, giving them contact with the reality of their future profession. Due to the inclusion of immigrant students in municipal and state schools in the city of Manaus (AM). In this study we aimed to understand the perception of Physical Education residents regarding the involvement of immigrant students in school physical education classes. We involved Physical Education residents from a Higher Education Institution, who were selected intentionally and for convenience. For data analysis, we used Discursive Textual Analysis (ATD) and also opted for a bibliographical review on the rights of immigrants to education in Brazil. We conclude that the growing diversity in classrooms due to migration highlights the urgency of better preparing teachers to serve immigrant students, including recognition and respect for cultural and linguistic diversity, adoption of pedagogical strategies to overcome language barriers, offering emotional support for migration trauma, addressing social and economic challenges, promoting equity and social justice. Furthermore, the need for teachers to master other languages, such as Libras, reflects the commitment to inclusive education, facilitating intercultural communication and ensuring full participation in education for students who are deaf or hard of hearing. Investing in teacher training aimed at inclusion not only strengthens pedagogical skills, but also contributes to a fairer and more welcoming society, where each student can reach their full potential.